Elementary School Students' Mathematics Learning Motivation in the Context of Educational Management: A Cross-Sectional Study with Rasch Analysis - Muhamad Suhardi; Mar'atus Sholihah; Rusi Rusmiati Aliyyah (Universitas Pendidikan Ganesha, 2025)
One element in educational process, that often becomes a concern is student learning motivation. This motivation includes internal and external drives that influence students' interests and abilities to be actively involved in the learning process. This study aims to investigate the learning motivation of 5th grade elementary school students in mathematics learning using Rasch model-based analysis. This study is a descriptive study with a cross-sectional design, involving 79 students as research subjects. Data were collected through a questionnaire designed to measure six main indicators of learning motivation, namely intrinsic value, achievement value, self-regulation, self-efficacy, utility value, and test anxiety. The results of the analysis showed that students' learning motivation was in the high category overall, with the Self-Efficacy (SE) indicator recording the highest score of 78%, followed by Utility Value (UV) of 73.5%. The self-regulation (SR) indicator showed a lower but still significant score of 70%. Rasch analysis showed that the questionnaire had a good level of reliability of 0.86 for items and 0.83 for respondents, as well as validity that was in accordance with the measurement model. These findings emphasize the importance of increasing students' self-confidence and supporting self-management in mathematics learning to improve learning motivation. The implications of these findings highlight the need to develop learning strategies that can strengthen students' self-confidence and reduce their anxiety during exams.